Applying negative ions to reduce surgical smoke in operation room. (October 2022) - Ninh, Xuan-Huy; Su, Jing-Wen; Lin, Hong-Yiou; Chen, Yung-Chung; Wang, Sheng-He; Guo, How-Ran; Kuo, Yao-Lung; Lin, Ming-Yeng
Abstract: Long-term exposure to surgical smoke generated from electrocautery can increase health risks for medical personnel. Surgical smoke contains high concentrations of nanoparticles (NP, diameter ≤200 nm) and particulate matters with diameter less than 2.5 μm (PM2.5 ), which can cause respiratory illnesses in medical personnel. Currently, local exhaust ventilation (LEV) is often used to reduce particles levels. However, LEV generates extra noise and can be easily blocked by blood clots formed during surgery. In this study, we added an ionizer to an electrosurgical pencil to help increase NP removal efficiency and compared the removal efficiency with that of a smoke evacuation pencil. The experiments were performed in an animal surgical facility in which air change rate, relative humidity, and temperature were controlled. We measured the PM2.5 and NP concentrations near the source and in the breathing zone. The ionizer alone, wall suction, smoke evacuation pencil, and wall suction plus ionizer reduce NP number concentrations by 80.1%, 84.5%, 90.3%, and 92.4%, respectively in the breathing zone. The respective reductions in PM2.5 were 86.5%, 92.9%, 93.0%, and 97.2%. Similar PM2.5 and NP removal efficiency was seen near the source. Wall suction plus ionizer shows the highest removal efficiency for NP and PM2.5, but the removal efficiency is not significantly higher ( p  > 0.05) than the commercial smoke evacuation pencil and wall suction. Moreover, excess lifetime carcinogenic risk also decreased by 79.1%, 90.7%, 93.0%, and 95.6% for the negative ions (NI), wall suction, smoke evacuation pencil, and NI + wall suction, respectively. The newly developed surgical smoke removal devices help reduce particle concentrations and thus can help protect the health of medical personnel. Graphical abstract: Image 1 Highlights: Negative ions can help reduce surgical smoke concentrations without generating additional noise. Adding negative ions to wall suction proves to be the most efficient method for reducing the particle number and mass concentrations in surgical smoke. Negative ions can be used in clinical practice or other workplaces that requires silence and efficient removal rates of nanoparticles.